Making Universal and Justice History at the National University, Costa Rica (2015-2025) - Torres Fauaz, Armando (2025)
This paper summarises the research itinerary of its author. It deals with subjects related to the History of Justice and the so-called Universal History, as they have been developed by the author in the framework of his research projects, financed by the Universidad Nacional (UNA), Cost Rica.